Comprehensive Sportsfest Assessment: Evaluating Facilities, Organization, Scheduling, and Athletic Experience - Mary Rose Montano; Ronald A. Gonzales; Aveto Dasal Jr.; Renante Artificio; Anna Rhea Opeña; Meljhon Mosca; Maria Mylin S. Miranda; Armando A. Salenga Jr. (Research Synergy Foundation Press, 2025)
Sports fests have traditionally promoted fitness, camaraderie, and athletic talent in schools, later expanding to organizations. The annual Sports Fest fostered collaboration through various activities. However, its impact had not been fully assessed. Key factors such as the quality of facilities, event organization, scheduling, and participant experiences were crucial in determining the overall success and reception of the event. This study evaluated the Sports Fest by examining participant satisfaction with facilities, organization, scheduling, and athletic experiences. It also assessed the achievement of goals related to activity takeaways, unity, teamwork, and student participation. The study explored the relationship between satisfaction and goal achievement, identified areas for improvement, and proposed an action plan to enhance future events. The study employed a descriptive-correlational mixed-methods design, utilizing surveys and qualitative feedback from 267 athletes selected through purposive sampling. Participants rated satisfaction on various aspects using a validated questionnaire, while open-ended questions captured qualitative feedback. Data were analyzed with descriptive statistics, Spearman's rho, and thematic coding, revealing themes such as the need for improved scheduling, enhanced facilities, and better communication for program development and improvement. The Sportsfest promoted athletic excellence, teamwork, and community engagement. Participants praised the focus on health, safety, organization, and inclusivity, but highlighted areas for improvement, such as facilities, scheduling, and officiating. Teamwork was identified as a key strength, while clearer rules, better communication, and improved venues were recommended to enhance satisfaction and unity. The study's limitation was its focus on athletes, excluding non-athletes and spectators, and its cross-sectional design, which limited trend analysis. While qualitative feedback was gathered, conducting in-depth interviews could have provided more detailed insights. External factors like social desirability bias and survey fatigue may have affected result accuracy. Future research could involve a more diverse participant pool, longitudinal methods, and a broader demographic analysis. This study's value lies in its potential to guide targeted improvements, ensuring future Sportsfests better align with participant needs and institutional goals. By addressing gaps in existing research, particularly in linking satisfaction with goal achievement, it contributes to the broader discourse on sports event management and its role in fostering community engagement and inclusivity.